A narrative review of autophagy in migraine - Huang, Yanan; Li, Hongyan; Yu, Qijun; Pan, Yonghui (Frontiers in Neuroscience, 2025)
Background and objectiveAutophagy is a natural process regulated by autophagy-related genes in eukaryotic cells that involves the degradation of cytoplasmic proteins and old or damaged organelles via the lysosomal pathway to help maintain cell homeostasis. Previous studies have suggested a potential association between autophagy and migraine, while the underlying mechanisms remain unclear. This review seeks to evaluate the possible involvement of autophagy in the pathophysiology of migraine, aiming to clarify its role and implications for future research and therapeutic strategies.MethodsA search in PubMed was conducted for English-language articles until December 5, 2024. Key terms of “autophagy,” “migraine,” “microglia,” “neurogenic inflammation,” “central sensitization,” “mitophagy” and “neuropathic pain” in different combinations.ResultsIn the context of migraine, the activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (PKB/Akt) signaling pathway exerts a direct influence on the mammalian target of rapamycin (mTOR), leading to a reduction in autophagy levels. Moreover, the stimulation of purinergic ligand-gated ion channel type 7 receptor (P2X7R) in microglia can hinder autophagy by interfering with the fusion of autophagosomes and lysosomes, which impedes the degradation of substrates within the autophagolysosome. Increased levels of calcitonin gene-related peptide (CGRP) may also modulate autophagy through the Akt/mTOR or protein kinase A (PKA)/mTOR signaling pathways. Additionally, research indicates that mitophagy may be partially impaired in individuals suffering from migraine. Furthermore, autophagy could contribute to the dysregulation of synaptic plasticity by influencing the processes of long-term potentiation (LTP) and long-term depression (LTD), both of which are associated with central sensitization in chronic migraine.ConclusionThese findings suggest that autophagy may play an important role in the pathophysiology of migraine, particularly in its development and central sensitization. Research on autophagy modulators related to migraine will provide valuable insights for treatment strategies.